DESCRIPTION OF ELDERLY VICTIMS OF ACUTE MYOCARDIAL INFACTION (Fiep Bulletin - online, 2016)
The population is facing the accelerated aging process, concerning our country as well as the whole humanity. The aim was to identify the prevalence of elderly patients who suffered AMI in 2013, along with the description of their profiles and the risk factors of elderly people assisted by an emergency service in a city in western Paraná. A descriptive and documentary research with quantitative approach was chosen. Data was collected through medical records of patients who were evaluated by the cardiology/hemodynamic services and who suffered acute myocardial infarction in the period of January to December of 2013 and collected in the second half of August 2014. The survey had shown that the profile of the elderly who suffered AMI among both genders are higher concentrated in the age group of 65 to 69 years old, among married and widowed. The prevalence was higher among men, being 32 (72.7%) and 12 women (27. 3%). As to the risk factors responsible for the development of cardiovascular diseases, it is observed that usually, hypertension and diabetes mellitus are related in Myocardial Infarction. Therefore, it is understood the importance of engaging managers with health professionals in order to adapt and improve a preventive health care to this demand as well as the needs of the population.
Keywords: Elderly; Description; Acute Myocardial Infarction (AMI)